«Інфраструктурна пастка» у житловій сфері України: техніко-економічні та споживчі оцінки - Пантелеєв, П. О.; Щербина, А. А. (Ways to Improve Construction Efficiency, 2013)
The problem of preserving and reproduction of multi flat housing in Ukraine taking into account the high level of amortization and low financial possibilities of population in conditions of private property of dwelling is considered. The methodology of appraisal of renovation needs balanced with population payment ability is proposed.